Chapter Comparar a Europa. O conceito de literatura europeia como fator de integração política - Magalhães, Gabriel (Libere carte, 2023)
Starting with the last European discourse of David Sassoli, our intention is to reflect on Europe, specifically, on the concept of European literature as a factor of political integration.